2021
DOI: 10.1038/s41598-021-85671-y
|View full text |Cite
|
Sign up to set email alerts
|

Distant metastasis time to event analysis with CNNs in independent head and neck cancer cohorts

Abstract: Deep learning models based on medical images play an increasingly important role for cancer outcome prediction. The standard approach involves usage of convolutional neural networks (CNNs) to automatically extract relevant features from the patient’s image and perform a binary classification of the occurrence of a given clinical endpoint. In this work, a 2D-CNN and a 3D-CNN for the binary classification of distant metastasis (DM) occurrence in head and neck cancer patients were extended to perform time-to-even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
4
28
2
Order By: Relevance
“…The inclusion of GTV differed from the original research the CNN comes from. In that study [ 30 ], the single slice with the most extensive area of the tumor was used for the 2D-CNN experiments. We decided to include all slices of the GTV also to develop the deep learning model because ovarian masses often have cystic components and considering a single slice may lead to losing many relevant pieces of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of GTV differed from the original research the CNN comes from. In that study [ 30 ], the single slice with the most extensive area of the tumor was used for the 2D-CNN experiments. We decided to include all slices of the GTV also to develop the deep learning model because ovarian masses often have cystic components and considering a single slice may lead to losing many relevant pieces of information.…”
Section: Discussionmentioning
confidence: 99%
“…As a second approach, we adopted the 2D-CNN built by Lombardo et al [ 30 ], which showed high performance in tumor classification. Image pre-processing was conducted in Python 3.7, while the 2D-CNN was implemented in Tensorflow 2.4.0.…”
Section: Methodsmentioning
confidence: 99%
“…Distant metastasis-free survival, de ned as the interval from the rst day of treatment to the date of the event, was the clinical endpoint in this study to demonstrate the reliability assessment of the radiomic model 27 . Previous studies of binary classi cation models of HNC 25,28 have achieved good prediction results but were limited because the time-to-event was neglected during model development.…”
Section: Methodsmentioning
confidence: 99%
“…A stratified three-fold cross-validation (S3FCV) strategy [59] was utilized to evaluate the classification performances. The random seed was set to 0.…”
Section: Stratified K-fold Cross Validation Strategymentioning
confidence: 99%